2010
DOI: 10.1007/s11596-010-0460-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective roles of α-lipoic acid in rat model of mitochondrial DNA4834bp deletion in inner ear

Abstract: The protective roles of alpha-lipoic acid in the rat model of mitochondrial DNA (mtDNA) 4834bp deletion in inner ear were investigated. Forty female Wistar rats at 4 weeks of age were divided into four groups: group A (D-galactose group, n=10), group B (D-galactose+alpha-lipoic acid group, n=10), group C (alpha-lipoic acid group, n=10), and group D (control group, n=10). Auditory brainstem response (ABR) was used to detect the hearing threshold. Colorimetry was used to analyze activity of superoxide dismutase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…These characteristics are considered to be associated with an increase in oxidative stress caused by a metabolic disturbance. Previous studies have established a mimetic aging model in the cochleae of rats following 8 weeks of D-gal treatment, and demonstrated that the activity levels of antioxidant enzymes decreased and those of lipid peroxidation increased in this model ( 20 22 ). Furthermore, the levels of mitochondrial DNA (mtDNA) common deletion (CD) were significantly increased in the cochleae of the D-gal-treated rats ( 20 24 ).…”
Section: Introductionmentioning
confidence: 88%
“…These characteristics are considered to be associated with an increase in oxidative stress caused by a metabolic disturbance. Previous studies have established a mimetic aging model in the cochleae of rats following 8 weeks of D-gal treatment, and demonstrated that the activity levels of antioxidant enzymes decreased and those of lipid peroxidation increased in this model ( 20 22 ). Furthermore, the levels of mitochondrial DNA (mtDNA) common deletion (CD) were significantly increased in the cochleae of the D-gal-treated rats ( 20 24 ).…”
Section: Introductionmentioning
confidence: 88%
“…Such damage by ROS is mediated by several oxidative stress-responsive signaling pathways and proinflammatory pathways including NF- κ B, JAK2/STAT3, JNK, IL-16, and IL-1, suggesting that those signaling molecules may be potential targets in protecting cells from noise-induced damage [ 9 11 ]. Moreover, ROS is known to deplete the intracochlear antioxidants and inhibit antioxidant enzymes including glutathione peroxidase [ 12 ], superoxide dismutases (SOD) [ 13 , 14 ], NQO1, catalase, and hemeoxygenase-1 (HO-1) [ 15 ]. Such antioxidant enzymes are key players in the defense system that living cells have developed to protect the hair cells against the destructive effects of ROS and have been targets for ototoxic stimuli including noise [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study investigating the effects of 17 antioxidant compounds (acetyl-L-carnitine (ALCAR), α-lipoic acid, β-carotene, carnosine, coenzyme Q10 (CoQ10), curcumin, d-α-tocopherol, epigallocatechin-3-gallate (EGCG), gallic acid, lutein, lycopene, melatonin, N-acetyl-L-cysteine (NAC), proanthocyanidin, quercetin, resveratrol and tannic acid) on the prevention of ARHL in mice, ARHL was almost completely prevented by treatment with α-lipoic acid and CoQ10; partially prevented by NAC treatment; and not prevented by the other compounds [43]. Other studies also support the positive preventive effects of α-lipoic acid and CoQ10 on ARHL through research in laboratory animals or human elderly subjects [101,103,104,105]. On the contrary, there are differences in opinion as to whether NAC is effective for the prevention of ARHL in mice [106,107].…”
Section: Mitochondria-targeted Antioxidants For Treatment Of Hearimentioning
confidence: 98%